Can The Effects Of Human Biases Employed By Investors To Select Securities Be Limited Through The Use Of Accounting Ratios As A Screening Process? - Francois, James (2012)
Since the creation of stock markets individuals have attempted to build a strategy which would be able to not only understand what has happened in markets, but what will happen going forward. Technical analysis has provided graphs and charts to statistically identify the trajectory of a security. However, all aspects of these decision making processes are subject to human emotions, for all aspects of the markets are driven by people. From this, the field of behavioural finance has been growing, to explain the key human traits present within markets that cause investment decisions to not be optimal. This study will analyse these heuristics and biases, and attempt to construct a trading strategy which aims to limit the risk of potential losses for investors. My proposal is that through a number of simple accounting ratios an investor can screen securities to identify which ones are being driven largely by sentiment, hence have inflated prices. Such a technique of screening securities is not exclusive, even the novice investor will be able to apply the techniques that this thesis will delve into. This is something I argue most investors can have access to, and therefore the question really becomes which strategy has a higher economic value, and whether that coincides with the investors’ motivations for being in the stock markets.